Analisis Proses Pembelajaran Model Kooperatif Tipe Jigsaw pada Materi Hidrokarbon di SMAN 6 Kota Jambi - Riyanti, Eka (Journal Evaluation in Education (JEE), 2022)
This study aims to determine the success of the implementation of the jigsaw cooperative learning model on hydrocarbon class X SMAN 6 Jambi City and to determine the factors that influence student success in using the jigsaw type cooperative learning model on class X hydrocarbon material at SMAN 6 Jambi City. This type of research is descriptive research. By using triangulation method in data processing. The results of this study are observations made 3 times, the percentage increases with each meeting. Based on the results of the questionnaire with indicators of supporting elements of the cooperative learning model, the implementation of learning and the role of the teacher which was carried out for 3 meetings, the results obtained were good. As for the learning outcomes obtained in the remaining 3 meetings, the highest learning outcomes were obtained at the third meeting of 89. Based on the overall findings, it can be concluded that students and teachers at SMAN 6 Jambi City are able to apply jigsaw type learning to hydrocarbon materials. The results of this study provide prospects for the importance of conducting further research in an effort to find the right strategy to apply the jigsaw in order to adapt the jigsaw to suit local educational conditions before being used in areas such as Jambi City.